2024
DOI: 10.1128/mbio.00159-24
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of growth medium for detecting drug interactions in Gram-negative bacteria that model in vivo responses

Kathleen P. Davis,
Yoelkys Morales,
Rachel J. Ende
et al.

Abstract: The rise in infections caused by multidrug-resistant (MDR) bacteria has necessitated a variety of clinical approaches, including the use of antibiotic combinations. Here, we tested the hypothesis that drug-drug interactions vary in different media, and determined which in vitro models best predict drug interactions in the lungs. We systematically studied pair-wise antibiotic interactions in three different media, CAMHB, (a rich lab medium standard for antibiotic susceptibility testi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 96 publications
0
2
0
Order By: Relevance
“…Additionally, synergistic or antagonistic interactions between different antibiotics depend on the composition of the environment. Understanding these interactions in vivo can inform the selection of combination therapies for difficult‐to‐treat infections (Davis et al., 2024 ).…”
Section: In Vivo Activity Of Antibioticsmentioning
confidence: 99%
“…Additionally, synergistic or antagonistic interactions between different antibiotics depend on the composition of the environment. Understanding these interactions in vivo can inform the selection of combination therapies for difficult‐to‐treat infections (Davis et al., 2024 ).…”
Section: In Vivo Activity Of Antibioticsmentioning
confidence: 99%
“…Only a few studies have explored interspecific variation of DDI scores ( Spitzer et al 2011 ; Robbins et al 2015 ; Brochado et al 2018 ; Davis et al 2024 ), but they have demonstrated that DC experiments (used to obtain DDI scores) could be scalable in the number of species and strains. A high-throughput study of DDIs in gram-negative bacteria has shown that synergies are more conserved across species than antagonisms and additive combinations ( Brochado et al 2018 ).…”
Section: Introductionmentioning
confidence: 99%